2019
DOI: 10.1108/ijhg-09-2018-0044
|View full text |Cite
|
Sign up to set email alerts
|

The role of national rural health mission in reducing infant mortality rate in India

Abstract: Purpose The purpose of this paper is to assess the role of National Rural Health Mission (NRHM) in reducing Infant Mortality in India. The study will help the government in deciding its future course of action regarding the infant mortality rate (IMR) reduction in India. Design/methodology/approach This paper adopts the interrupted time series analysis (ITSA) approach with a control group to study the role of NRHM in reducing the IMR in India. The authors examined infant mortality in rural areas of India for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This rate of decline was reported to be higher in bigger states, similar to the results we found 28 . The post‐NHM implementation phase has been reported to have a 0.6%–2% higher rate of decline per annum in IMR as compared to the pre‐NHM period 29–31 . Difference in rate of decline in IMR between urban and rural areas has also been reported to narrow down after the implementation of NHM 31 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This rate of decline was reported to be higher in bigger states, similar to the results we found 28 . The post‐NHM implementation phase has been reported to have a 0.6%–2% higher rate of decline per annum in IMR as compared to the pre‐NHM period 29–31 . Difference in rate of decline in IMR between urban and rural areas has also been reported to narrow down after the implementation of NHM 31 .…”
Section: Discussionsupporting
confidence: 86%
“…The post‐NHM implementation phase has been reported to have a 0.6%–2% higher rate of decline per annum in IMR as compared to the pre‐NHM period 29–31 . Difference in rate of decline in IMR between urban and rural areas has also been reported to narrow down after the implementation of NHM 31 . However, most of these studies were based on computation of a mean annual rate of reduction, unlike the ARIMA model coupled with interrupted time‐series approach that we employed.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Moreover, the National Rural Health Mission (NRHM) has contributed significantly to reducing infant mortality in rural India. 23 Various studies have highlighted that NRHM has significantly reduced the healthcare inequalities in India. 24 Mother's education and open defecation were the top two contributors to inequality in infant mortality in India during 2015-16.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that NRHM in India succeeded in reducing the IMR gap between urban and rural areas. This time-series analysis further explained a decrease in IMR several years before the implementation of NRHM which helped accelerate it (Pandey and Mohan, 2019).…”
Section: Resultsmentioning
confidence: 66%
“…The fourth and sixth studies took place in India and discussed the NRHM using different approaches. NRHM is a scheme created by the central government that aims to reduce IMR in India by strengthening delivery services at the village level (Pandey and Mohan, 2019). Other programs have been launched under this scheme.…”
Section: Resultsmentioning
confidence: 99%